2017
DOI: 10.1111/bph.13792
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic landscape related to reactive oxygen species formation in the cardiovascular system

Abstract: *Authors contributed equally.Cardiovascular diseases are among the leading causes of death worldwide. Reactive oxygen species (ROS) can act as damaging molecules but also represent central hubs in cellular signalling networks. Increasing evidence indicates that ROS play an important role in the pathogenesis of cardiovascular diseases, although the underlying mechanisms and consequences of pathophysiologically elevated ROS in the cardiovascular system are still not completely resolved. More recently, alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
119
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(142 citation statements)
references
References 238 publications
(336 reference statements)
0
119
1
Order By: Relevance
“…In conclusion, we have designed and validated a method to screen metabolites and chemicals for their effect on global methylation of newly synthesized DNA. Our results reveal a mechanism by which neutrophil-derived oxidants could inhibit maintenance methylation and thereby influence the course of disease (34)(35)(36).…”
Section: Discussionmentioning
confidence: 80%
“…In conclusion, we have designed and validated a method to screen metabolites and chemicals for their effect on global methylation of newly synthesized DNA. Our results reveal a mechanism by which neutrophil-derived oxidants could inhibit maintenance methylation and thereby influence the course of disease (34)(35)(36).…”
Section: Discussionmentioning
confidence: 80%
“…ROS can directly convert 5-methylcytosin (5mC) to 5-hydroxymethylcytosine (5hmC) which blocks the activity of DNMT1 leading to an improper methylation inheritance during mitosis and global hypomethylation (144). Moreover ROS can oxidize guanosine to 8-oxo-20-deoxyguanosine (8-oxodG) thus inhibiting methylation of adjacent cytosine and further contributing to global hypomethylation of DNA (145,146). The formation of 8-oxodG in particular loci promotes the transcription of pro-inflammatory genes in response to TNF-α (147).…”
Section: Mitochondrial Ros and Epigenetic Changesmentioning
confidence: 99%
“…It contains the active methyl-donor group utilized by most methyltransferase enzymes. It has been demonstrated that ROS can reduce SAM availability, thus limiting the activity of DNA and histone methyltransferases (145). This is achieved either by inhibiting methionine adenosyl-transferase and thus SAM synthesis or by inhibiting methionine synthase and thus methionine regeneration (56).…”
Section: S-adenosylmethioninementioning
confidence: 99%
“…The ageing of the population will gradually increase the incidence of cardiovascular diseases, which seriously affects human health. In many physiological activities of the cardiovascular system, ROS are important signalling molecules that maintain the homeostasis of the internal environment of the cardiovascular system . A significant increase in ROS levels is closely related to the occurrence and development of cardiovascular diseases including heart failure, atherosclerosis, hypertension and ischaemic heart disease .…”
Section: Introductionmentioning
confidence: 99%